The human capital selection of young males seeking asylum in Germany - Martin Lange; Friedhelm Pfeiffer (Journal for Labour Market Research, 2019)
This study analyses the selection of a sample of 203 young male asylum seekers from Middle Eastern and African countries that recently arrived in Germany. The findings suggest that, on average, asylum seekers in our sample have 22% more years of schooling-the indicator used for human capital-when compared to same-aged males from their country of origin. In addition, the analysis suggests that asylum seekers in the sample often accumulated rather low or relatively high levels of schooling compared to same-aged males in their countries of origin. This phenomenon is even more pronounced for parental education. It is demonstrated that individual human capital influences short-run integration outcomes in Germany. The paper discusses potential economic explanations for the findings on immigrant selection and integration outcomes.
Keywords: F22; J15; J24; 330; Immigrant selection; Asylum seekers; Human capital; Family background; Integration